rPSGL-1-Ig, a recombinant PSGL-1-Ig fusion protein, ameliorates LPS-induced acute lung injury in mice by inhibiting neutrophil migration - Shao, H-Z; Qin, B-Y (Cellular and Molecular Biology, 2015)
The binding of selectin to P-selectin glycoprotein ligand-1 (PSGL-1) mediates the tethering and rolling of leukocytes on the endothelium during leukocyte migration and inflammation. Recombinant human PSGL-1-Ig fusion protein (rPSGL-1-Ig) is a widely used selectin inhibitor that prevents neutrophil entry into inflamed or reperfused tissues. We hypothesized that rPSGL-1-Ig could be used to as a drug for the treatment of acute lung injury (ALI). We induced murine ALI by injecting mice with lipopolysaccharide (LPS) and then treated the mice with rPSGL-1-Ig. We determined the lung injury index, wet/dry ratio, and inflammatory cytokine level in differentially treated mice. The symptoms of LPS-induced lung injury were alleviated by rPSGL-1-Ig treatment. The histopathological index of LPS-induced lung injury improved after rPSGL-1-Ig treatment. rPSGL-1-Ig treatment also reduced the recruitment of inflammatory cells, including neutrophils, into the lung, as well as reducing the level of inflammatory cytokines. These data suggest that rPSGL-1-Ig protein has a therapeutic effect on LPS-induced lung injury.